Urban poverty and habitat precariousness in the Caribbean - Rajack, Robin (ECLAC SantiagoCL, 2004)
Focuses on urban poverty and habitat precariousness in the Caribbean countries with an emphasis on current and former British territories. Looks at the different sets of related indicators. Analyzes available information by countries mainly referred to habitat conditions such as housing, sanitation, land titles, water, public services, in order to present an evaluation of poverty conditions and precariousness in Caribbean urban areas. Analyzes also, land markets in the Caribbean countries. Develops guidelines for improving regularization policies in the Caribbean region.